3R MoS2 with Broken Inversion Symmetry: A Promising Ultrathin Nonlinear Optical Device. Issue 30 (7th June 2017) - Shi, Jia; Yu, Peng; Liu, Fucai; He, Peng; Wang, Rui; Qin, Liang; Zhou, Junbo; Li, Xin; Zhou, Jiadong; Sui, Xinyu; Zhang, Shuai; Zhang, Yanfeng; et al.
Abstract : Nonlinear 2D layered crystals provide ideal platforms for applications and fundamental studies in ultrathin nonlinear optical (NLO) devices. However, the NLO frequency conversion efficiency constrained by lattice symmetry is still limited by layer numbers of 2D crystals. In this work, 3R MoS2 with broken inversion symmetry structure are grown and proved to be excellent NLO 2D crystals from monolayer (0.65 nm) toward bulk‐like (300 nm) dimension. Thickness and wavelength‐dependent second harmonic generation spectra offer the selection rules of appropriate working conditions. A model comprising of bulk nonlinear contribution and interface interaction is proposed to interpret the observed nonlinear behavior. Polarization enhancement with two petals along staggered stacking direction appears in 3R MoS2 is first observed and the robust polarization of 3R MoS2 crystal is caused by the retained broken inversion symmetry. The results provide a new arena for realizing ultrathin NLO devices for 2D layered materials. Abstract : A 2D van der Waals crystal (3R MoS2 ) can serve as a promising ultrathin nanoscale frequency doubling crystal under phase matching conditions. Thickness and wavelength‐dependent second harmonic generation spectrum of 3R MoS2 offers the selection rules of appropriate working conditions. Polarization enhancement with two petals along staggered stacking direction appears in 3R MoS2 is observed.